Role of distal diabetic polyneuropathy in the development of media calcification in patients with diabetesmellitus - Natalya Alexandrovna Molitvoslovova; Gagik Radikovich Galstyan (Сахарный диабет)
Arterial media calcification is a common finding in diabetes mellitus (DM) and is associated with distal symmetric neuropathy. Arterialcalcification also emerges as a complication of chronic kidney disease and is considered to be a risk factor for cardiovascular andgeneral morbidity. "Calcification" is actually not an accurate term, because morphologic alterations also include bone tissue formationor "ossification". Both processes are complex and exist in tight connection with bone homeostasis. Connection between distal symmetricneuropathy and arterial calcification suggests that neuropathy may be an independent risk factor for cardiovascular morbidity.